Vivienda colectiva con zócalo comercial y cultural - Navarro Flores, Sara Micaela (2020)
The constant transformation of the city of Quito has allowed us to visualize remarkable urban growth, historically several milestones have been determining the activities to be established around them and because of the disuse and loss of their relevance they have generated disconnection and insolation of the mention sectors which throughout time tend to cause the lack of control over the quality of public space and increases insecurity. As a response to this problematic the ARO 860 2019-1 workshop intervenes with the purpose to restructure the urban system through a Master Plan which has as an incentive to understand the concept that inhabiting requires spaces that involve the inclusion of social components which share harmonically among themselves and can take advantage of the dynamic diversity in areas with dominant activities considered clusters. The degree project is located between 10 de Agosto Avenue and Río Cofanes street where the Y old station facilities are located currently. Close to this place is the bullring which has been without use for seven years. Due to the need of implementing housing and activities to reactivate the sector the intention to inhabit spaces that generates voids is born. This, in turn, will enable the dynamic of social interaction in the sector to be strengthened, being cultural expressions, the ones that generate identity. The commercial contribution is the way that produces the appropriation of space while the development of households allows individual growth.